Borderless Sound, Bordered Reality: Crossfaith and the Dynamics of Transnationalism in Japanese Metalcore - Belia, Athaya Prita; Puryanti, Lina; Husain, Sarkawi B (Vocational College of Diponegoro University, 2025)
This paper examines the cross-border dynamics of Japanese metalcore, focusing particularly on the band Crossfaith, exploring how they navigate the complexities of global mobility, cultural identity, and transnationalism in their music. This study employs a case study approach, using document analysis as the primary method. The data then was analyzed by identifying recurring themes, patterns, and relationships. The results show that while metalcore itself is already transnational due to its use of English, Crossfaith exemplifies the creation of a